Cell proliferation is a key determinant of the outcome of FOXO3a activation. - Poulsen, R; Carr, A; Hulley, P (2015)
The FOXO family of forkhead transcription factors have a pivotal role in determining cell fate in response to oxidative stress. FOXO activity can either promote cell survival or induce cell death. Increased FOXO-mediated cell death has been implicated in the pathogenesis of degenerative diseases affecting musculoskeletal tissues. The aim of this study was to determine the conditions under which one member of the FOXO family, FOXO3a, promotes cell survival as opposed to cell death. Treatment of primary human tenocytes with 1 pM hydrogen peroxide for 18 h resulted in increased protein levels of FOXO3a. In peroxide-treated cells cultured in low serum media, FOXO3a inhibited cell proliferation and protected against apoptosis. However in peroxide treated cells cultured in high serum media, cell proliferation was unchanged but level of apoptosis significantly increased. Similarly, in tenocytes transduced to over-express FOXO3a, cell proliferation was inhibited and level of apoptosis unchanged in cells cultured in low serum. However there was a robust increase in cell death in FOXO3a-expressing cells cultured in high serum. Inhibition of cell proliferation in either peroxide-treated or FOXO3a-expressing cells cultured in high serum protected against apoptosis induction. Conversely, addition of a Chk2 inhibitor to peroxide-treated or FOXO3a-expressing cells overrode the inhibitory effect of FOXO3a on cell proliferation and led to increased apoptosis in cells cultured in low serum. This study demonstrates that proliferating cells may be particularly susceptible to the apoptosis-inducing actions of FOXO3a. Inhibition of cell proliferation by FOXO3a may be a critical event in allowing the pro-survival rather than the pro-apoptotic activity of FOXO3a to prevail.